Physical fitness and body fatness are associated with mental health in Korean young adults: a cross sectional study - Oh, Minsuk; Kang, Dong-Woo; Kim, Dong-Il; Lee, Junga; Yoon, Seok; Kim, YoonMyung; Chung, Kyong-Mee; Lee, Hae-Dong; Lee, Ji-Won; Jeon, Justin Y. (International Journal Of Community Medicine And Public Health, 2018)
Background: It has been recognized that body fatness and mental disorders have association, however very limited evidence have proved that physical fitness and mental health have association. Relationship between physical fitness and mental health in young adults has not been fully proved. The purpose of the study was to investigate the association between physical fitness, body fatness, and mental health in young adults. Methods: A total of 149 (97 males and 52 females) college students were included. Physical fitness (sit-ups, push-ups, 1 mile run/walk), and body mass index (BMI) was measured, and psychological questionnaires including life satisfaction, self-efficacy, the beck depression inventory (BDI), and adult self report (ASR) were administered. The levels of physical fitness and BMI were classified into tertile groups and were analyzed. Results: Female participants with the highest tertile of BMI had highest ASR score (p<0.05). Participants with highest level of physical fitness showed higher level of self-efficacy in both males and females (p<0.05). In both male and female, physical fitness was a significant predictor for self-efficacy (Male: β=0.35, p<0.05, Female: β =0.31, p<0.05). Conclusions: In conclusion, physical fitness and body fatness were associated with mental health. Especially, physical fitness, independent of BMI, was proved as significant indicator for mental health in young adults.